Post-Covid-19 Marketing Management Strategy In Digital Business - Zet Ena; Devi Trihandari Widyatania; Hermyn Benny Hina (International Journal of Management and Business Economics, 2023)
This study analyzes business strategies using digital marketing after the Covid-19 pandemic. The research was carried out using a descriptive qualitative approach with the type of literature review research. The primary data sources for this research are digital marketing books and journals related to the marketing business. How to collect data by collecting several relevant research journal articles. This data analysis uses content. The study results show that in the post-covid-19 pandemic, there has been a habit of people who like to shop online. There is a need for a business strategy to deal with this and maintain the existence of a digital marketing business. Business strategies can be implemented for online companies as a digitalization strategy using digital marketing by implementing search engine marketing, digital content marketing, Pay-per-click Ads, and influencer marketing. The recommendations from this study require digital business applications that are easily accessible to all levels of society.